2012
DOI: 10.1128/jcm.05531-11
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Tropheryma whipplei in Culture-Negative Endocarditis

Abstract: "Classical" Whipple's disease (cWD) is caused by Tropheryma whipplei and is characterized by arthropathy, weight loss, and diarrhea. T. whipplei infectious endocarditis (TWIE) is rarely reported, either in the context of cWD or as isolated TWIE without signs of systemic infection. The frequency of TWIE is unknown, and systematic studies are lacking. Here, we performed an observational cohort study on the incidence of T. whipplei infection in explanted heart valves in two German university centers. Cardiac valv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 32 publications
(42 reference statements)
4
87
1
11
Order By: Relevance
“…However, one should be aware that PAS staining has a poor specificity in brain biopsy samples (130,177). Depending on the localization of the infection, T. whipplei can also be found in bone marrow, lymph nodes, skin, liver, muscle, eye, and lung (10,62,103,113,120,137,178). It is important to realize that in chronic localized infections, PAS-stained duodenal biopsy specimens may be negative (102,130,162,179,180).…”
Section: Histopathology (Pas and Hematoxylin-and-eosin Stain [Hande]mentioning
confidence: 99%
See 2 more Smart Citations
“…However, one should be aware that PAS staining has a poor specificity in brain biopsy samples (130,177). Depending on the localization of the infection, T. whipplei can also be found in bone marrow, lymph nodes, skin, liver, muscle, eye, and lung (10,62,103,113,120,137,178). It is important to realize that in chronic localized infections, PAS-stained duodenal biopsy specimens may be negative (102,130,162,179,180).…”
Section: Histopathology (Pas and Hematoxylin-and-eosin Stain [Hande]mentioning
confidence: 99%
“…In 255/1,135 (22%) of the cases, a bacterial cause could be established by a combination of molecular methods and culture. Surprisingly, 16/255 (6.3%) of the patients with a proven bacterial infection (1.5% of the total population) carried T. whipplei, making it the fourth most frequent pathogen identified from these proven infectious cases (103). Follow-up of these patients revealed that most of these T. whipplei-positive patients displayed no symptoms of classic Whipple's disease and had thus neither been diagnosed nor treated properly for their potentially lethal T. whipplei infection.…”
Section: Localized Chronic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…T. whipplei causes up to 6% of cases of culture-negative endocarditis (7,20,21). C. acnes, a rare cause of endocarditis, may cause culture-negative endocarditis due to the requirement for prolonged blood culture incubation for growth of some strains (14); in addition, some strains may not grow in blood cultures.…”
Section: Diagnosis Of Culture-negative Endocarditismentioning
confidence: 99%
“…A forma mais comum de apresentação é uma síndrome de má absorção, com diarreia e perda ponderal frequentemente associados a dor abdominal, febre, linfadenopatias periféricas e abdominais 3,5,6 . O envolvimento cardíaco na DW pode afectar qualquer estrutura, estando essencialmente descritos casos de endocardite, com a maioria diagnosticada após análise das válvulas ressecadas 7,8,9 . A sintomatologia osteoarticular está presente em cerca de 90% dos casos, geralmente precede o diagnóstico em cerca de 10 anos e caracteriza-se por oligo ou poliartralgias simétricas, migratórias, não destrutivas e seronegativas.…”
Section: Discussionunclassified